Decision Quality Questionnaire: An Instrument to Measure the Quality of Your Decision in Professional Life - Laurensia, Fiona; Yuniarti, Kwartarini Wahyu; Darwin, Muhadjir; Sumaryono, Sumaryono (Dinasti International Journal of Management Science, 2024)
Research objectives so that the quality of decisions made by leaders in the organization can be measured using valid and reliable measurement tools measured by using valid and reliable measuring instruments. Method literature review, questionnaire formulation, validity & reliability test validity & reliability of the questionnaire. Results The questionnaire is valid and reliable to be used as a measuring tool for Decision Quality. Contribution this study aims to provide a research instrument that is to measure Decision Quality. The quality of the decision is the quality that results from the results of the decision that has been applied or tested to the maximum and the results are seen to the maximum and assessed to the maximum as well. From the results of data processing using SPSS, it produces a Scale Statistics Mean of 46.8829, Variance 41.133, Std Deviation 6.41352, Validity respondent 205, Crochbach Alpa 0.888. Product Moment Correlation coefficient or rcount > 0.3, so it can be said that all statement items on the questionnaire have good validity. Meanwhile, the entire Cronbach's Alpha coefficient value obtained for all items is > 0.872 so it can be stated that all statement items on the questionnaire have good reliability (> 0.6).